Preliminary study to investigate Salmonella sp. and E. Coli O157:H7 in ground beef sold in supermarkets in Puebla city, Mexico - Cabrera-Maldonado, Carlos (Universidad Autónoma de Tamaulipas, 2013)
It is accepted that the presence of pathogen bacteria in food products made out of bovine is a human health risk because these microorganisms are capable of producing gastrointestinal diseases. This kind of pathology is the main cause of medical consultation and death in Mexico and the world. The present study sought to find the presence of Salmonella sp. and Escherichia coli O157:H7 in 20 samples of ground beef, obtained at random in supermarkets in the city of Puebla, Mexico. The methodologies used were the ones described in the Mexican Official Standards: aerobic mesophilic bacteria (NOM-092-SSA1-1994) and Salmonella sp. (NOM-114-SSA1-1994), including the steps of pre-enrichment, selective enrichment, differential and enriched media inoculation, biochemical and serological identification. Even though neither Salmonella sp. nor E. coli O157:H7 strains were identified, the use of molecular techniques is recommended to make an exhaustive search of these pathogen agents, not only in ground beef, but also in other cattle-derived products.